Geoelectrical structures beneath Spitsbergen-Svalbard derived from magnetotelluric imaging - Beka, Thomas Ibsa (UiT Norges arktiske universitet, 2016)
Paper II, III and IV of this thesis is not available in Munin. Paper II: Beka, T. I., Smirnov, M., Birkelund, Y., Senger, K., Bergh, S. G.: 3-D Magnetotelluric imaging of Central Svalbard, Norway. (Manuscript). Published version, with title "Analysis and 3D inversion of magnetotelluric crooked profile data from central Svalbard for geothermal application" available in Tectonophysics 2016. Paper III: Beka, T. I., Bergh, S. G., Smirnov, M., Birkelund, Y.: Magnetotelluric signatures of the complex Tertiary fold-thrust belt and extensional fault architecture beneath the Brøgger peninsula, Svalbard. (Manuscript). Paper IV: Beka, T. I., Senger, K., Autio, U. A., Smirnov, M., Birkelund, Y.: Integrated electromagnetic data investigation of a Mesozoic CO2 storage target reservoir-cap rock succession, Svalbard. (Manuscript). Published version available in Journal of Applied Geophysics 2017, 136:417–430. In this thesis a series of geophysical surveys are carried out on the geologically important and remote Svalbard using magnetotelluric imaging, to constrain better the geology particularly defining geothermal resources. Magnetotellurics (MT) relays on natural source time-varying electric and magnetic field data measured at the earth’s surface in order to derive the subsurface resistivity structure. As part of the thesis, broadband MT data are collected in central and northwestern Spitsbergen in the period range between 0.003 - 1000 s from nearly 80 stations distributed along five profiles of 6 - 42 km long. The new MT data have brought significant contributions to extend the existing crustal scale geological knowledge, which mostly inferred from surficial, seismic and gravity studies in the past. From the MT data, we derived 2D and 3D resistivity models for selected areas and enabled to image the structure of the near surface bedrock geology and crustal scale architecture. The 2D and 3D inversion results indicated reasonable agreement with previous geological data, models and well reflected tectonic histories. Within the ...